Winston Churchill : Personal Accounts of the Great Leader at War - Paterson, Michael (Cincinnati, Ohio David & Charles, 2005)
Offers an insight into the life of Winston Churchill, from his escape as a prisoner of war in South Africa, his political career, his dark days following the Dardanelles failure, and his resurgence as Britain's great wartime Prime Minister. This work juxtaposes Churchill's prolific commentaries on himself with the opinions of those who knew him.
Include Illustration and Index
Keywords: Prime ministers -- Soldiers -- Great Britain -- Churchill, Winston, 1874-1965